2011
DOI: 10.5688/ajpe75351
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Pharmacogenomics Educational Needs of Pharmacists

Abstract: Objectives. To evaluate the self-perceived knowledge and confidence of inpatient and outpatient pharmacists in applying pharmacogenomics information to clinical practice. Methods. A 19-question multiple-choice, electronic needs-assessment survey instrument was distributed to 480 inpatient and outpatient pharmacists in a large, academic, multi-campus healthcare system. Results. The survey response rate was 64% (303). Most respondents (85%) agreed that pharmacists should be required to be knowledgeable about pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
192
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 172 publications
(209 citation statements)
references
References 25 publications
17
192
0
Order By: Relevance
“…We analyzed a subset of responders (n5181) from our original needs assessment to determine if the 2 groups were similar and found that the demographics of the large group were not different from those of the postsurvey data (n584). 13 Although we had a lower-than-expected matched-survey response rate, the responders to the post-education survey instrument were representative of those who responded to an earlier survey instrument with respect to work setting, percent of time spent at bedside, and years in practice. The results of this study, therefore, are generalizable to the large population of health system pharmacists who we previously assessed.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We analyzed a subset of responders (n5181) from our original needs assessment to determine if the 2 groups were similar and found that the demographics of the large group were not different from those of the postsurvey data (n584). 13 Although we had a lower-than-expected matched-survey response rate, the responders to the post-education survey instrument were representative of those who responded to an earlier survey instrument with respect to work setting, percent of time spent at bedside, and years in practice. The results of this study, therefore, are generalizable to the large population of health system pharmacists who we previously assessed.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 This task was achieved by addressing an educational gap that was identified as a result of the needs assessment for inpatient and outpatient pharmacists.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations